AN ANALYSIS OF PROBLEMS FACED BY FIRST YEAR STUDENTS OF STKIP MUHAMMADIYAH MUARO BUNGO IN WRITING CAUSE AND EFFECT ESSAY - ARINI KUMALA SARI (Jurnal Muara Pendidikan, 2018)
The purpose of this article is to present the result of a study conducted to describe analysis of problem faced by first year students of STKIP Muhammadiyah Muaro Bungo in writing cause and effect essay. This study was a descriptive research design. This research conducted by involving all students of first year students of English Department of STKIP Muhammadiyah Muaro Bungo academic year 2017/2018. Instrument of research were writing test and interview. The findings showed that the students got low score in writing cause and effect essay. It was shown that 16 students ( 88,89%) had difficulties in writing cause and effect essay. There were 12 students (66,67%) had difficulties in organizing ideas, 16 students (88,89%) had difficulties in using correct grammar, 10 students ( 55,56%) had difficulties in using appropriate words, 14 students ( 77,77% ) had difficulties in using transition goal, 9 students ( 50 % ) had difficulties in using mechanics. The causes of this problem were Interlingua transfer, intralingua transfer and vocabulary. Thus, the researchers expect that the writing lecturers are able to give good writing technique, and the students can do more exercises to increase their skill in writing.